The burnout-depression conundrum: investigating construct-relevant multidimensionality across four countries and four patient samples. - De Beer, Leon T.; Hakanen, Jari J.; Schaufeli, Wilmar B.; De Witte, Hans; Glaser, Jürgen; Kaltiainen, Janne; Seubert, Christian; Morin, Alexandre J. S. (Psychology & Health, 2025)
This research seeks to contribute to the ongoing discussion about the distinctive nature of burnout and depression. In a first study, we relied on employee samples from four European countries (N = 5199; 51.27% women; Mage = 43.14). In a second study, we relied on a large sample of patients (N = 5791; 53.70% women; Mage = 39.54) who received a diagnosis of burnout, depressive episode, job strain, or adaptation disorder. Across all samples and subsamples, we relied on the bifactor exploratory structural equation modelling to achieve an optimal disaggregation of the variance shared across our measures of burnout and depression from the variance uniquely associated with each specific subscale included in these measures. Our results supported the value of this representation of participants' responses, as well as their invariance across samples. More precisely, our results revealed a strong underlying global factor representing participants' levels of psychological distress, as well as the presence of equally strong specific factors supporting the distinctive nature of burnout and depression. This means that, although both conditions share common ground (i.e. psychological distress), they are not redundant. Interestingly, our results also unexpectedly suggested that suicidal ideation might represent a distinctive core component of depression.